Análise do uso dos recursos naturais na reserva extrativista marinha Mocapajuba, município de São Caetano de Odivelas, Pará - PINHEIRO, Vanessa da Conceição (2020)
The Mocapajuba Marine Extractive Reserve (Resex-Mar), located in the municipality of São Caetano de Odivelas, northeastern Pará, is a recent Conservation Unit (UC). It was created in 2014 to be administered by the Chico Mendes Institute for Biodiversity Conservation. One of the goals of Resex-Mar Mocapajuba's creation is to ensure the sustainable use of natural resources and to protect the livelihoods and culture of the region's traditional extractivist communities. The present work aimed to map the natural resources used by the traditional populations within the Reserve, as well as to identify the ways of exploitation of these resources. Through data obtained from interviews with 10 family units, five of which are from the island of São dos Ramos and the other five of São Miguel Island, it was possible to identify that the main activities practiced by the traditional populations within Resex-Mar are: fishing, crustacean collection, subsistence agriculture and vegetal extraction. Among the most used resources by communities are: 20 fish species, 3 crustacean species, 3 plant species. With respect to land use in agriculture, 26 fruit species, 10 vegetable species, and cassava, chicken, ducks and pigs were identified. Fishing, crustacean collection, and agriculture are done manually. The most traded products are fishery and crustacean collection products, but trade is not practiced by all families in the community.